Get sh*t done : the ultimate guide to productivity, procrastination, & profitability - Gitomer, Jeffrey, 1946- (John Wiley & Sons, Inc., 2020)
"Everyone wants to do more, and as a result be more and have more. This book, Get Sh*t Done, will have a profound effect on anyone looking to understand and implement the elements of greater productivity, get the answers to what causes procrastination, and achieve an understanding of the formula that productivity minus procrastination leads to PROFIT. The book itself will outline and define a step-by-step process of achievement beginning with attitude and take the reader through the success elements of belief, desire, determination, goals, productivity, resilience, achievement, and fulfillment. But the book would not be complete without totally defining and presenting game plans for the elimination of the destructive elements of productivity and achievement: procrastination and reluctance. The architecture of the book will make reading easy and enjoyable and the central messages and challenges presented in this information packed book will be both transferrable to the reader and easy to implement. To grab the reader from the first page of the book, the traditional "introduction" will be renamed "To DO or Doo Doo, that is not just the question, it's the question, the opportunity and the outcome. And the epilog will be "watch your step if you wanna step into success. The best part of Get Shit Done, is that it's for everyone in every walk of life. Every one has a "to do list," or a project, or an assignment, or a goal, or a plan, or a dream. This book will get everyone from "do" to "done."--